Pengaruh Implementasi ISO 9001:2015 Klausul Tujuh tentang Sumber Daya Manusia terhadap Kinerja Karyawan - Usman, Usman (https://jurnal.binamandiri.ac.id/, 2023)
This study aims to assess the effect of implementing the ISO 9001:2015 quality management system, especially clause seven relating to human resources, on the performance of employees in the production department of PT. XYZ. This study uses an associative quantitative approach. The research sample consisted of 85 employees selected using the Slovin calculation method. Data collection was carried out through primary data by observing and distributing questionnaires to respondents. In addition, secondary data collection was also carried out through literature study. The results showed that the implementation of clause seven of ISO 9001:2015 had a significant effect on the performance of employees in the production department of PT. XYZ.